Optisol-GS Storage of Cultured Human Limbal Epithelial Cells at Ambient Temperature Is Superior to Hypothermic Storage. (1st December 2020) - Jackson, Catherine Joan; Pasovic, Lara; Raeder, Sten; Sehic, Amer; Roald, Borghild; de la Paz, Maria F.; Tønseth, Kim Alexsander; Utheim, Tor Paaske
ABSTRACT: Purpose: To investigate the feasibility of using Optisol-GS as a convenient, xenogeneic-free alternative for storage of cultured human limbal epithelial cells (HLECS) for use in treatment of limbal stem cell deficiency (LSCD). In the present study, we compared storage of cultured HLEC using the conventional hypothermic Optisol-GS storage method at 4°C versus storage at 23°C (room temperature). Materials and Methods: HLECs were cultured for three weeks on amniotic membrane (AM), transferred to polypropylene containers and stored in Optisol-GS for 4 days at 23°C and 4°C. A calcein-acetoxymethyl ester/ethidium homodimer-1 assay was used to assess viability. Morphology and phenotype were analyzed by light microscopy and immunohistochemistry, respectively. Results: Expression of stem cell and proliferation markers p63, ∆Np63α, ABCG2, K19, K3, Cx43, Ki67, and PCNA was maintained at pre-storage control levels during storage at 23°C. ABCG2 and PCNA expression were both significantly altered during storage at 4°C. HLEC cell sheet viability also significantly declined following storage at 4°C. HLEC sheets stored at 4°C demonstrated extensive detachment of basal cells from the AM in sharp contrast to storage at 23°C, where attachment to the AM was maintained throughout the storage period. Conclusions: The present study demonstrates the feasibility of short-term storage of cultured HLECs in Optisol-GS, which offers a convenient standardized xenogeneic-free storage method. Storage temperature highly affected the results. Maintenance of cell viability, morphology and undifferentiated proliferative phenotype of cultured HLEC sheets favored storage at 23°C.